(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A continuous late Eocene through Oligocene carbonate sequence was recovered at Ocean Drilling Program (ODP) Site 1218 in the paleo-equatorial Pacific Ocean. The preservation history of selected calcareous nannofossil species across the Eocene/Oligocene (E/O) boundary is presented together with late Eocene and Oligocene calcareous nannofossil biochronology. The astronomically calibrated timescale of Pälike et al. (2006) is used here. Across the E/O boundary, placolith preservation is controlled by variation in carbonate content. Taxa less prone to dissolution are Reticulofenestra umbilicus, Coccolithus pelagicus, Ericsonia formosa and Dictyococites bisectus, while Cyclicargolithus floridanus is more susceptible to dissolution. A biochronologic framework has been established for the following taxa: the highest occurrences (HO) of Discoaster barbadiensis (34.773 Ma), D. saipanensis (34.435 Ma), E. formosa (32.919 Ma), R. umbilicus (32.021 Ma), Sphenolithus predistentus (26.928 Ma), S. distentus (26.812 Ma), and S. ciperoensis (24.432 Ma), and the lowest occurrences (LO) of S. distentus (29.997 Ma) and S. ciperoensis (27.142 Ma). The first consistent appearance of Triquetrorhabdulus carinatus occurs at 26.556 Ma, while the onset of the peak interval of T. carinatus was determined at 24.669 Ma. Biochronological comparisons are made with other sites from the Atlantic Ocean. A Triquetrorhabdulus morphotype, labeled as T. aff. carinatus, was recorded for the first time in the studied sediments, and precedes the LO of T. carinatus by 0.7 Myr. Its stratigraphic range has a duration of about 3.3 Myr. T. aff. carinatus disappears concomitantly with the beginning of a sharp increase in abundance of T. carinatus.